Implementasi Business Intelligence Untuk Menganalisis Data Proses Manufaktur Menggunakan Google Data Studio - Tumini Tumini; Endang Sri Subekti (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to apply the concept of Business Intelligence (BI) by implementing it using Google Data Studio tools in analyzing production data. The BI approach utilizes technology and analytical methods to collect, integrate, analyze, and present the business information needed by company leaders. Google Data Studio is the latest BI platform and provides convenience in interactive data visualization. In this study, the implementation of BI was carried out using Google Data Studio to analyze cardboard box production data. This approach involves the process of collecting production data from various related sources, such as manufacturing systems, inventory systems, and sales systems. The data is then integrated and presented in the form of an interactive and easy-to-understand visualization. The research method used includes literature studies on BI concepts and technology, as well as experiments using Google Data Studio to analyze the production data that has been collected. During the experiment, various indicators of production performance were identified and analyzed, such as productivity, efficiency and error rate. The results of this analysis are interpreted to gain valuable insights in improving production processes and making better business decisions. It is hoped that this research will provide a better understanding of BI implementation using Google Data Studio in the context of production data analysis. It is hoped that the findings of this research can become the basis for companies to obtain better information and make more effective decisions in improving production performance.